The Predicament of Language and Culture: Advocacy, Anthropology, and Dormant Language Communities. (2nd December 2018) - Schwartz, Saul
Abstract : A growing literature in linguistic anthropology critically examines the rhetoric of endangered language advocacy. A number of themes remain underexplored, however, including the invocation of "culture" to justify language preservation, the interests of communities without fluent heritage language speakers, and anthropology's contribution to potentially problematic advocacy tropes. Discourses like "language is the core of culture" and "when a language dies, a culture dies" are widespread in language activism even though they undermine communities' efforts to maintain distinctive cultural identities in the wake of language shift and put dormant language communities in a double bind. While Boasian anthropology contains anti‐essentialist and counter‐nationalist perspectives on language, culture, and race, some Herderian advocacy tropes are borrowed from the (also Boasian) tradition of linguistic relativity in its popular Whorfian iteration. Drawing on my research on Chiwere language politics, I identify two forms of agency available to endangered and dormant language communities: one form of agency resists language loss but accepts dominant ideologies of national difference that make heritage languages essential to indigenous cultural identities, while another form of agency accepts language loss but resists Herderian nationalist expectations that authentic indigenous communities speak their traditional languages. [advocacy rhetoric, dormant language communities, language and culture ideologies, agency, Chiwere]